Chile’s Agricultural Innovation System : An Action Plan Towards 2030 - World Bank (World Bank, 2012)
The report builds on the 'towards a vision for agricultural innovation in Chile in 2030' report and is further based on a series of background papers and a consultation process that took place between December 2010 and May 2011. The current study is the third in a series of three that were agreed between the Government of Chile and the World Bank to support the development of a long-term agricultural innovation strategy. The first paper reviewed the functioning of the three main public technological institutes and recommended how their performance can be improved. The second study explored the future of Chile's agriculture towards 2030, using scenario planning and developing a vision for the future of its agricultural innovation system. This paper is based on the results of the former two studies, as well as a set of background documents and further consultations, and will outline the action plan required to achieve the aforementioned vision. The objective of this action plan is to enhance the capacity of Chile's agricultural innovation system in order to achieve the goals as laid out in the vision for the sector for the year 2030. It builds on the current strengths of the agricultural innovation system and elaborates on the main actions needed to address the priority topics. Five principles serve as the foundation of the plan: recognizing national and regional responsibilities; distinguishing public and private roles; diversity; excellence; and institutional integration. Most of the actions can be implemented between 2011 and 2015 and consolidated in the next five years. After 2020, plans and activities can be revised in the light of the progress obtained up to that moment.